2019
DOI: 10.1042/cs20190156
|View full text |Cite
|
Sign up to set email alerts
|

The pseudogene PTENP1 regulates smooth muscle cells as a competing endogenous RNA

Abstract: The long non-coding RNA (lncRNA) PTENP1 is a pseudogene of phosphatase and tensin homologue deleted on chromosome ten (PTEN), has been implicated in smooth muscle cell (SMC) proliferation and apoptosis. PTENP1 is the pseudogene of PTEN. However, it is unclear whether and how PTENP1 functions in the proliferation and apoptosis of human aortic SMCs (HASMCs). Here, we hypothesised that PTENP1 inhibits HASMC proliferation and enhances apoptosis by promoting PTEN expression. PCR analysis and Western blot assays res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…However, compared with other members of lncRNAs, transcribed pseudogenes-derived lncRNAs have not been paid attention previously. Recent studies have demonstrated that transcribed pseudogenederived lncRNAs play important roles in multiple biological processes, such as cell proliferation, cell cycle, cell migration and cell death (Lai et al, 2019;Oliveira-Mateos et al, 2019;Varesio et al, 2019).…”
Section: Origination and Classification Of Pseudogenes And Pseudogenementioning
confidence: 99%
“…However, compared with other members of lncRNAs, transcribed pseudogenes-derived lncRNAs have not been paid attention previously. Recent studies have demonstrated that transcribed pseudogenederived lncRNAs play important roles in multiple biological processes, such as cell proliferation, cell cycle, cell migration and cell death (Lai et al, 2019;Oliveira-Mateos et al, 2019;Varesio et al, 2019).…”
Section: Origination and Classification Of Pseudogenes And Pseudogenementioning
confidence: 99%
“…Nevertheless, the risks and consequences of an alteration of the pseudogenes were underrated. For example, PTEN, a gene implicated in cancer, has been edited by several teams (Wang et al, 2015;Hill et al, 2017), without final sequencing of its pseudogene PTENP1 even though PTENP1 is acting as a ceRNA of PTEN (Lai et al, 2019). Kawamura and colleagues were confronted with issues related to pseudogene homology when undertaking the CRISPR-Cas9 KO of NANOG which has 10 pseudogenes (Kawamura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PTENP1 and its parental gene, PTEN , were found to be upregulated in human aortic dissection samples. In this case PTENP1 also works as a microRNA sponge competing for miR-21 with parental gene transcripts, and overexpression of lncRNA results in elevated level of PTEN protein [ 81 ].…”
Section: Retro-lncrnas and Other Diseasesmentioning
confidence: 99%